Multiple solutions of nonlinear Neumann inclusions - Cianciaruso, Filomena; Pietramala, Paolamaria (Topological Methods in Nonlinear Analysis, 2023)
We prove new results on the existence of multiple solutions for elliptic inclusions with nonlinear boundary conditions of Neumann type. Our approach is topological and relies on the fixed point index for multivalued map.